Isolating membrane, battery and electric device
By introducing a substrate containing chelating groups and a functional layer of positively charged groups into the battery isolation film, the problems of insufficient battery reliability and cycle performance are solved, and higher battery performance and stability are achieved.
Patent Information
- Application Number
- CN202310903802.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-21
AI Technical Summary
In battery applications, the battery has poor reliability and cycle performance.
An isolation film is used that includes a base material and a functional layer. The base material is composed of a polymer film and an organic structure connected to its surface. The organic structure contains chelating groups; the functional layer contains positively charged groups that can react with the transition. Metal ions produce electrostatic repulsion and coordinately combine with transition metal ions through chelating groups to form chelates.
It improves the reliability and cycle performance of battery cells, reduces the risk of migration and precipitation of transition metal ions, and slows down the self-discharge rate of the battery.
Smart Images

Figure CN119340608A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an isolation film, a battery and an electrical device. Background Art
[0002] Batteries have the characteristics of high capacity and long life, so they are widely used in electronic devices such as mobile phones, laptops, battery cars, electric cars, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes and electric tools, etc. As batteries have made great progress, higher requirements are placed on battery performance. In order to improve battery performance, the isolation membrane in the battery is usually optimized and improved.
[0003] However, currently when the separator is applied to batteries, the battery reliability and cycle performance are still poor. Summary of the invention
[0004] The present application provides a separation film, a battery and an electrical device, and the use reliability and cycle performance of the battery described in the present application can be improved.
[0005] In a first aspect, an embodiment of the present application proposes an isolation membrane, which includes a substrate and a functional layer arranged on at least one side of the substrate, the substrate includes a polymer film and an organic structure connected to the surface of the polymer film, the organic structure includes a chelating group; the functional layer includes a positively charged group.
[0006] Therefore, the isolation membrane of the embodiment of the present application includes a substrate and a functional layer arranged on at least one side of the substrate, the substrate includes a polymer film and an organic structure connected to the surface of the polymer film, the organic structure includes a chelating group; the functional layer includes a positive charge group. When the isolation membrane is applied to a battery cell, the functional layer has a positive charge, which can produce a strong electrostatic repulsive force on the transition metal ions, and the transition metal ions are more likely to be retained by the functional layer on the side of the functional layer facing the positive electrode plate; the chelating group contained in the substrate can combine with the transition metal ions through coordination to form a chelate, stabilize the transition metal ions in the chelate, further reduce the risk of transition metal ions migrating to the negative electrode plate, and alleviate the risk of transition metal ions precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved.
[0007] In some embodiments, the functional layer includes a porous structure, and the average pore size of the porous structure is a nanometer-scale pore size; optionally, the average pore size of the porous structure is 1.0 nm to 3.0 nm. When the average pore size of the porous structure is within the above range, it is beneficial to further improve the retention effect of the functional layer on transition metal ions.
[0008] In some embodiments, the thickness of the functional layer is 10 nm to 50 nm. The introduction of the functional layer can not only improve the interception capacity of transition metal ions, but also improve the mechanical properties of the isolation membrane to a certain extent and improve the structural strength of the isolation membrane.
[0009] In some embodiments, the positive charge group includes at least one of an imide group, an amide group, and an imine group; optionally, the functional layer containing the imide group includes at least one of polyimide and polyetherimide; the functional layer containing the amide group includes at least one of polyamide, polyetheramide, polyacrylamide, polyarylene sulfide sulfoneamide, and polyarylene sulfide ketoneamide; the functional layer containing the imine group includes at least one of polyethyleneimine and polymethylpropyleneimine. The functional layer of the above-mentioned material is conducive to improving the overall thermal stability of the isolation membrane and the wetting performance in the electrolyte.
[0010] In some embodiments, the organic structure is disposed on the surface of the polymer film; or the organic structure is grafted onto the surface of the polymer film. The organic structure and the polymer film have a strong bonding ability, and the connection stability between the organic structure and the polymer film is higher.
[0011] In some embodiments, based on the total mass of the substrate, the mass percentage of the organic structure is 2% to 10%. The mass percentage of the organic structure within the above range can impart excellent chelating ability to the substrate.
[0012] In some embodiments, the chelating group may include at least one of a carboxyl group and an imino group; optionally, the organic structure containing the carboxyl group includes at least one of ammonium acrylate, 2-methyl-2-acrylic acid ammonium salt, methacrylic acid, crotonic acid, 3-methylcrotonic acid, 4-methyl-3-pentenoic acid, (E)-4-(4-methylpiperazine-1-yl)2-butenoic acid; optionally, the organic structure containing the imino group includes at least one of iminodiacetic acid, diethyl iminodiacetic acid, iminotriacetic acid), 3,3'-iminodipropionic acid, disodium iminodiacetic acid and 3-[(aminoiminomethyl)thio]propionic acid.
[0013] The coordination effect between the above-mentioned groups and transition metal ions is stronger, which is beneficial to stabilizing the transition metal ions in the isolation membrane.
[0014] In some embodiments, the weight average molecular weight of the organic structure is less than or equal to 1000Da, and can be 100Da to 900Da. The relatively small weight average molecular weight of the organic structure is conducive to improving the success rate of grafting the organic structure to the polymer film, and the connection stability between the organic structure and the polymer film is higher.
[0015] In some embodiments, the thickness of the substrate is less than or equal to 16 μm, and can be 5 μm to 14 μm. The functional layer of the embodiment of the present application is conducive to improving the overall mechanical properties of the separator, so that a thinner substrate can be selected, thereby helping to improve the energy density of the battery cell.
[0016] In some embodiments, the polymer film includes at least one of a polyolefin-based polymer and an ionic polymer fiber; optionally, the polyolefin-based polymer includes at least one of polyethylene, polypropylene, and polyvinylidene fluoride. Alternatively, the ionic polymer includes at least one of polyethyleneimine, polyvinylamine, polyphosphazene, and polyoxymethylene. The above types of polymers have a higher success rate of grafting with organic structures.
[0017] In a second aspect, an embodiment of the present application further provides a battery, wherein the battery cell comprises an isolation membrane as described in any embodiment of the first aspect of the present application.
[0018] In a third aspect, an embodiment of the present application further proposes an electrical device, comprising a battery as described in any embodiment of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0020] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.
[0021] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.
[0022] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.
[0023] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0024] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0025] Figure 6 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0026] The drawings are not necessarily drawn to scale.
[0027] The following are the descriptions of the reference numerals:
[0028] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;
[0029] 5. Battery cell; 51. Housing; 52. Electrode assembly;
[0030] 53. Cover plate;
[0031] 6. Electrical equipment. DETAILED DESCRIPTION
[0032] Hereinafter, the embodiments of the isolation membrane, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0033] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0034] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0035] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0036] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0037] The battery cell includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The separator is located between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet and the negative electrode sheet. The positive electrode sheet includes a positive electrode active material. The positive electrode active material is a donor of active ions such as sodium ions and lithium ions provided by the battery cell. The negative electrode sheet is an acceptor of active ions. The electrolyte provides a migration path for active ions between the positive electrode sheet and the negative electrode sheet. During the production process of battery cells and during the charging process of battery cells, transition metal ions in the positive electrode active material can dissolve in the electrolyte. On the one hand, the dissolution of transition metal ions may cause the structural collapse of the positive electrode active material and reduce the structural stability of the positive electrode plate. On the other hand, the migration of transition metal ions to the surface of the negative electrode plate through the electrolyte may cause the SEI film on the surface of the negative electrode plate to be destroyed, thereby increasing the risk of side reactions caused by direct contact between the negative electrode plate and the electrolyte, and reducing the cycle stability of the battery cell. On the other hand, transition metal ions may precipitate on the surface of the negative electrode plate to form metal dendrites. The growth of metal dendrites may pierce the isolation membrane of the battery cell, resulting in direct contact between the positive electrode plate and the negative electrode plate, causing a short circuit, reducing the reliability of the battery cell, and the self-discharge rate of the battery cell is too fast, which deteriorates the cycle performance of the battery cell.
[0038] In view of the above problems, the embodiment of the present application proposes an isolation membrane, which includes a substrate and a functional layer arranged on at least one side of the substrate, wherein the substrate includes a polymer film and an organic structure connected to the surface of the polymer film, wherein the organic structure includes a chelating group; the functional layer includes a positively charged group. When the isolation membrane is applied to a battery cell, the functional layer has a positive charge, which can produce a strong electrostatic repulsive force on transition metal ions, and the transition metal ions are more likely to be retained by the functional layer on the side of the functional layer facing the positive electrode plate; the chelating group contained in the substrate can combine with the transition metal ions through coordination to form a chelate, stabilize the transition metal ions in the chelate, further reduce the risk of transition metal ions migrating to the negative electrode plate, and alleviate the risk of transition metal ions precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved. Next, the technical solution of the present application is described in detail.
[0039] Isolation film
[0040] In a first aspect, an embodiment of the present application proposes an isolation membrane, which includes a substrate and a functional layer arranged on at least one side of the substrate, wherein the substrate includes a polymer film and an organic structure connected to the surface of the polymer film, and the organic structure includes a chelating group; the functional layer includes a positively charged group.
[0041] The substrate includes two surfaces facing each other along the thickness direction of the isolation film, and the functional layer can be arranged on either one of the two surfaces or on both surfaces.
[0042] The isolation membrane includes a substrate and a functional layer, and the functional layer is arranged on one of the two surfaces of the substrate. In this case, when the isolation membrane is applied to a battery cell, the substrate of the isolation membrane can be arranged closer to the positive electrode sheet relative to the functional layer, that is, the functional layer is located on the side of the substrate away from the positive electrode sheet; or the functional layer of the isolation membrane can be arranged closer to the positive electrode sheet relative to the substrate, that is, the substrate is located on the side of the functional layer away from the positive electrode sheet.
[0043] First, let's take the substrate as being located on the side of the functional layer away from the positive electrode sheet as an example. During the charging process of the battery cell, the active ions in the positive electrode sheet, such as lithium ions and sodium ions, are released from the positive electrode active material and migrate toward the negative electrode sheet. The transition metal ions in the positive electrode sheet, such as nickel ions, cobalt ions, and manganese ions, may also be dissolved from the positive electrode active material into the electrolyte and migrate toward the negative electrode sheet. When the active ions and transition metal ions move to the isolation membrane between the positive electrode sheet and the negative electrode sheet, since the functional layer of the isolation membrane has a positive charge, and the active ions and transition metal ions also have a positive charge, the active ions and transition metal ions are subject to electrostatic repulsion. The valence state of the active ions is usually low, such as monovalent, and the electrostatic repulsion force they are subject to is relatively small, that is, the effect of electrostatic repulsion on the active ions is relatively small. The active ions can still migrate from the functional layer to the negative electrode sheet; since the valence state of transition metal ions is usually high, for example, above positive divalent, they are subject to a large electrostatic repulsion force, and are more likely to be retained by the functional layer on the side of the functional layer facing the positive electrode sheet; under the retention effect of the functional layer, there may still be a risk of some transition metal ions migrating toward the negative electrode sheet. In this case, the chelating groups contained in the substrate can combine with the transition metal ions through coordination to form a chelate, and stabilize the transition metal ions in the chelate, further reducing the risk of transition metal ions migrating to the negative electrode sheet, and alleviating the risk of transition metal ions precipitating on the surface of the negative electrode sheet to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, thereby improving the cycle performance of the battery cell.
[0044] Secondly, the functional layer is located on the side of the substrate away from the positive electrode plate. During the charging process of the battery cell, when the active ions and transition metal ions move to the isolation membrane between the positive electrode plate and the negative electrode plate, the chelating groups contained in the substrate of the isolation membrane can combine with the transition metal ions through coordination to form a chelate, thereby stabilizing the transition metal ions in the chelate, and reducing the risk of the transition metal ions further moving toward the negative electrode plate; even if some transition metal ions are not fixed by the substrate in time, the functional layer will further retain the transition metal ions between the functional layer and the substrate through repulsion, thereby further promoting the formation of chelates between the substrate and the transition metal ions, thereby reducing the risk of transition metal ions migrating to the negative electrode plate, and alleviating the risk of transition metal ions precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, thereby improving the cycle performance of the battery cell.
[0045] Of course, if the isolation membrane includes a substrate and a functional layer, and the functional layer is arranged on both surfaces of the substrate, in this case, the isolation membrane's interception and stabilization effect on transition metal ions can be further enhanced, thereby further alleviating the risk of transition metal ions precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, thereby improving the cycle performance of the battery cell.
[0046] The positively charged groups have a good charge repulsion effect on high-valent transition metal ions, which can alleviate the migration of transition metal ions through the isolation membrane to the negative electrode to a certain extent. The metal dendrites formed on the surface of the negative electrode pierce the isolation membrane and cause self-discharge. When the chelating group is introduced on the isolation membrane at the same time, the chelating group can fix and adsorb the transition metal ions repelled by the positively charged groups well, because the repulsive effect of the positively charged groups can reduce the migration rate of the transition metal ions, which can reserve a longer reaction time for the chelating groups to fix and adsorb the transition metal ions, thereby significantly improving the ability of the chelating groups to fix and adsorb transition metal ions. Therefore, the positively charged groups and the chelating groups act together on the transition metal ions to play a good synergistic role, which can significantly improve the ability to adsorb and remove transition metal ions.
[0047] In some embodiments, the functional layer includes a porous structure, and the average pore size of the porous structure is a nanometer-scale pore size, for example, the average pore size is less than 10 nm. The functional layer is a porous structure, which is conducive to the smooth migration of active ions between the positive electrode sheet and the negative electrode sheet through the porous structure; compared with active ions, the ion radius of transition metal ions is generally larger, and transition metal ions are more easily trapped by nanometer-scale pores on the side of the functional layer close to the positive electrode sheet, thereby improving the interception effect of the functional layer.
[0048] Optionally, the average pore size of the porous structure may be 1.0 nm to 3.0 nm. When the average pore size of the porous structure is within the above range, it is beneficial to further improve the interception effect of the functional layer on transition metal ions.
[0049] Illustratively, the average pore size of the porous structure can be 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2.0 nm, 2.1 nm, 2.2 nm, 2.3 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.7 nm, 2.8 nm, 2.9 nm, 3.0 nm, or a range consisting of any two of the above values.
[0050] In the embodiment of the present application, the average pore size of the functional layer has a meaning well known in the art and can be measured using equipment and methods well known in the art. For example, a 1 mm by 1 mm area in the isolation membrane is taken as a sample, and its pore size is counted by observing it through a scanning electron microscope SEM; the average pore size can be calculated by taking multiple samples and taking the average pore size as the average pore size.
[0051] In some embodiments, the thickness of the functional layer is 10 nm to 50 nm. The introduction of the functional layer can not only improve the interception capacity of transition metal ions, but also improve the mechanical properties of the isolation membrane to a certain extent and improve the structural strength of the isolation membrane.
[0052] Exemplarily, the thickness of the functional layer can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm or a range consisting of any two of the above values.
[0053] In some embodiments, the positively charged group includes at least one of an imide group, an amide group and an imine group. The functional layer of the above material is conducive to improving the overall thermal stability of the isolation membrane and the wetting performance in the electrolyte.
[0054] Exemplarily, the functional layer containing the imide group includes at least one of polyimide PI and polyetherimide.
[0055] Exemplarily, the functional layer containing the amide group includes at least one of polyamide PA, polyether amide, polyacrylamide, polyarylene sulfide sulfone amide and polyarylene sulfide ketone amide.
[0056] Exemplarily, the functional layer containing the imine group includes at least one of polyethyleneimine PEI and polymethylpropyleneimine PMI.
[0057] In some embodiments, the thickness of the substrate may be less than or equal to 16 μm, and may be 5 μm to 14 μm. The functional layer of the embodiment of the present application is conducive to improving the mechanical properties of the isolation membrane as a whole, so that a thinner substrate can be selected, thereby helping to improve the energy density of the battery cell. Exemplarily, the thickness of the substrate can be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 12 μm, 15 μm, 16 μm, or a range consisting of any two of the above values.
[0058] In some embodiments, the porosity of the substrate is greater than or equal to 25%. When the porosity of the substrate is within the above range, the air permeability of the substrate can be guaranteed to be conducive to the migration of active ions, and because the porosity is relatively small, the mechanical properties of the substrate can also be guaranteed, providing good support for the functional layer.
[0059] In some embodiments, the polymer film may include at least one of a polyolefin-based polymer (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), and an ionic polymer. Exemplarily, the ionic polymer includes at least one of polyethyleneimine, polyethyleneamine, polyphosphazene, and polyoxymethylene.
[0060] Optionally, the polymer film may include a polyolefin-based polymer, which has a higher success rate of grafting with an organic structure. The substrate may be a single-layer film or a multi-layer composite film. When the substrate is a multi-layer composite film, the materials of each layer may be the same or different. The substrate formed by the above polymer has good chemical stability and mechanical stability.
[0061] The substrate includes a polymer film and an organic structure connected to the surface of the polymer film. The connection may refer to the organic structure being arranged on the surface of the polymer film as an independent organic compound, for example, the organic structure is coated on the surface of the polymer film to form a coating, and the coating is arranged on the surface of the polymer film; the connection may also refer to the organic structure being grafted onto the polymer film. In this case, the organic structure may refer to a group (for example, a group obtained after an organic compound loses a hydrogen atom), that is, the organic structure is grafted onto the side chain of the polymer of the polymer film to perform graft modification on the polymer film, thereby giving the polymer film the function of the organic structure. Optionally, the substrate includes a polymer film and an organic structure grafted onto the surface of the polymer film. This connection method makes the connection stability between the organic structure and the polymer film higher, and the chelating group in the organic structure can chelate with the transition metal ions through coordination, and chelate the transition metal ions between molecules and within molecules, so that the coordination between the chelating group and the transition metal ions is enhanced, and the transition metal ions are not easily separated, thereby effectively reducing the number of transition metal ions migrating to the negative electrode sheet.
[0062] The side chains of the polymer in the above polymer film are grafted and modified by an organic structure, the organic structure includes a chelating group with a chelating effect, and the introduction of the organic structure can give the substrate surface a chelating ability. In some embodiments, based on the total mass of the substrate, the mass percentage of the organic structure is 2% to 10%, and the mass percentage of the organic structure within the above range can give the substrate excellent chelating ability.
[0063] Illustratively, the mass percentage of the organic structure can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or a range consisting of any two of the above values.
[0064] In some embodiments, the chelating group may include at least one of a carboxyl group and an imino group. The coordination effect between the above groups and the transition metal ions is stronger, which is beneficial to stabilize the transition metal ions in the isolation membrane.
[0065] It should be noted here that the organic structure may only include chelating groups; the organic structure may also include other groups in addition to the chelating groups, that is, the organic structure is composed of the chelating groups and other groups. For example, the organic structure is a group formed after the organic compound is grafted onto the polymer film. For example, during the grafting process, the organic compound may lose hydrogen atoms to form the organic structure.
[0066] Optionally, the organic structure containing the carboxyl group includes at least one of ammonium acrylate, 2-methyl-2-acrylate ammonium salt, methacrylic acid, crotonic acid, 3-methylcrotonic acid, 4-methyl-3-pentenoic acid, and (E)-4-(4-methylpiperazine-1-yl)2-butenoic acid.
[0067] Optionally, the organic structure containing an imino group includes at least one of iminodiacetic acid, diethyl iminodiacetate, iminotriacetic acid), 3,3'-iminodipropionic acid, disodium iminodiacetate, and 3-[(aminoiminomethyl)thio]propionic acid.
[0068] In some embodiments, the organic structure may further include active ions such as lithium ions, sodium ions, etc. The active ions can be combined with the chelating group through coordination. When the separator is applied to a lithium-ion battery monomer, the lithium ions can be released from the organic structure, which is beneficial to replenishing the active lithium ions in the battery system. When the separator is applied to a sodium-ion battery monomer, the sodium ions can be released from the organic structure, which is beneficial to replenishing the active sodium ions in the battery system.
[0069] In some embodiments, the ratio of the molar content of active ions to the molar content of chelating groups is 0.01 to 1:1.
[0070] In the embodiment of the present application, the group type in the substrate can be measured by infrared spectroscopy. For example, the infrared spectrum of the material can be tested to determine the characteristic peaks contained therein, thereby determining the type of the modified group. Specifically, the material can be subjected to infrared spectroscopy analysis using instruments and methods known in the art, for example, using an infrared spectrometer (such as the IS10 Fourier transform infrared spectrometer of Nicolet, USA), and tested according to the general rules of GB / T 6040-2019 infrared spectroscopy analysis method.
[0071] In some embodiments, the substrate has an infrared spectrum of 1708.4 cm -1 , which indicates the presence of carboxyl groups.
[0072] In some embodiments, the substrate has an infrared spectrum at 1400 cm -1 Up to 1450cm -1 , which indicates the presence of an imino group.
[0073] In some embodiments, the weight average molecular weight of the organic structure is less than or equal to 1000Da, and can be 100Da to 900Da. The relatively small weight average molecular weight of the organic structure is conducive to improving the success rate of grafting the organic structure to the polymer film, and the connection stability between the organic structure and the polymer film is higher.
[0074] Illustratively, the weight average molecular weight of the organic compound can be 100 Da, 110 Da, 120 Da, 130 Da, 140 Da, 150 Da, 160 Da, 170 Da, 180 Da, 190 Da, 200 Da, 210 Da, 220 Da, 230 Da, 240 Da, 250 Da, 260 Da, 270 Da, 280 Da, 290 Da, 300 Da, 310 Da, 320 Da, 340 Da, 350 Da, 360 Da, 370 Da, 380 Da, 390 Da. 900 Da, 920 Da, 950 Da, 960 Da, 980 Da, 1000 Da or a range consisting of any two of the above values.
[0075] In the present application, the weight average molecular weight of an organic structure is a well-known meaning in the art and can be tested using equipment or methods known in the art. Specifically, the weight average molecular weight of an organic compound can be tested by gel permeation chromatography (GPC). Specifically, the GPC1515 instrument of Waters Company of the United States is used for testing, the sample is dissolved in tetrahydrofuran, the dissolution time is more than 12h, the concentration of the sample is 4mg / ml, the sample is filtered and prepared, the test temperature is 25°C, and the test flow rate is 1ml / min for testing.
[0076] In some embodiments, the isolation film may further include a heat-resistant coating layer, and the heat-resistant coating layer may include inorganic particles.
[0077] Exemplarily, the isolation film includes a substrate and a functional layer, the functional layer is arranged on one of the two surfaces of the substrate, and the heat-resistant coating can be located between the substrate and the functional layer, or on the side of the functional layer facing away from the substrate, or on the side of the substrate facing away from the functional layer.
[0078] Exemplarily, the isolation film includes a substrate and a functional layer, the functional layer is disposed on two surfaces of the substrate, and the heat-resistant coating can be located between the substrate and the functional layer, or on a side of the functional layer facing away from the substrate.
[0079] In some embodiments, the mass percentage of the inorganic particles in the heat-resistant coating is less than or equal to 30%. For example, the mass percentage of the inorganic particles in the heat-resistant coating is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the above values.
[0080] The inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.
[0081] In some embodiments, inorganic particles having a dielectric constant of 5 or more may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Tin O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT).
[0082] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass (0<x<4, 0<y<13), lanthanum lithium titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).
[0083] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, olivine-structured lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.
[0084] In some embodiments, the heat-resistant coating may further include a binder. As an example, the binder may include at least one of an aqueous solution type acrylic resin (e.g., acrylic acid, methacrylic acid, sodium acrylate monomer homopolymer or copolymer with other comonomers), polyvinyl alcohol (PVA), isobutylene-maleic anhydride copolymer, and polyacrylamide.
[0085] In some embodiments, the thickness of the heat-resistant coating may be 0.1 μm to 4 μm, optionally 0.5 μm to 3 μm. This helps to improve the energy density of the battery cell. In the present application, the thickness of the heat-resistant coating refers to the thickness of the heat-resistant coating located on a single side of the substrate. Exemplarily, the thickness of the heat-resistant coating may be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range consisting of any two of the above values.
[0086] It should be noted that the functional layer parameters and heat-resistant coating parameters (such as thickness, etc.) of the above-mentioned isolation membrane are the functional layer parameters on one side of the substrate and the heat-resistant coating parameters on one side of the substrate. When the functional layer parameters are set on both sides of the substrate, the functional layer parameters on either side meet the requirements of this application and are considered to fall within the protection scope of this application. When the heat-resistant coating parameters are set on both sides of the substrate, the heat-resistant coating parameters on either side meet the requirements of this application and are considered to fall within the protection scope of this application.
[0087] Method for preparing isolation film
[0088] In a second aspect, an embodiment of the present application provides a method for preparing an isolation film, the method comprising:
[0089] Step S100, providing a polymer film;
[0090] Step S200, disposing an organic structure on the surface of the polymer film, and connecting the organic structure to the surface of the polymer film to form a substrate, wherein the organic structure includes a chelating group;
[0091] Step S300 , disposing a functional layer containing positively charged groups on at least one side of the polymer film.
[0092] In some embodiments, in step S100, the organic structure is connected to the surface of the polymer film by grafting. Specifically, the organic structure can be grafted to the surface of the polymer film by ultraviolet light grafting, initiator initiation, etc. Optionally, ultraviolet light grafting is used, which is more convenient to operate and has a higher grafting success rate.
[0093] In some embodiments, after step S200, the method may further include treating the substrate obtained in step S200 with a lithium hydroxide aqueous solution, and then washing the substrate with deionized water until the pH value is about 7.0, so that the substrate contains lithium ions. It can be understood that at least part of the chelating groups are coordinated with the lithium ions to form a substrate modified with a lithium-based chelate compound. The lithium ions can replenish lithium to the system during the charge and discharge process, which is beneficial to improve the capacity of the battery cell.
[0094] In some embodiments, in step S300, a functional layer can be formed on a polymer film by interfacial polymerization. Specifically, a solution containing polymerization monomers is placed on the surface of the polymer film (the surface is a surface modified with an organic structure) to initiate polymerization of the polymerization monomers to form a functional layer. Alternatively, the functional layer can be formed by coating a polymer solution on a polymer film and drying it.
[0095] Battery Cell
[0096] In a third aspect, an embodiment of the present application provides a battery cell, wherein the battery cell includes a separator. The separator may include a separator according to any embodiment of the first aspect of the present application or a separator prepared by a method according to any embodiment of the second aspect of the present application, and the separator serves to isolate the positive electrode sheet from the negative electrode sheet. By using the separator, the reliability, self-discharge performance, and cycle performance of the battery cell can be improved.
[0097] [Positive electrode]
[0098] In some embodiments, the battery cell further includes a positive electrode tab.
[0099] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0100] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.
[0101] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0102] In some embodiments, the positive electrode active material may be a positive electrode active material for a battery cell known in the art. As an example, the positive electrode active material may include at least one of the following materials, a layered positive electrode active material (e.g., ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich / sodium layered and rock salt phase layered materials), an olivine-type phosphate active material, a spinel structured positive electrode active material (e.g., spinel lithium manganate, spinel nickel lithium manganate, lithium-rich spinel lithium manganate, and lithium nickel lithium manganate, etc.).
[0103] For example, the general formula of the layered positive electrode active material is Li x A y Ni a Co b Mn c M (1 -abc)Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y includes one or more of O and F. Specifically, the layered positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, and the like.
[0104] Optionally, the layered positive electrode active material is a ternary material, for example, 0<a≤1, 0<b≤1, 0<c≤1, illustratively, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) or more.
[0105] For example, the general formula of the olivine phosphate active material is Li x A y Me a M b P 1-c X c Y z, wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; and Y includes one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0106] For example, the general formula of the positive electrode active material of the spinel structure is Li x A y Mn a M 2-a Y z , wherein 0≤x≤2, 0≤y≤1, and 0.9≤x+y≤2; 0.5≤a≤2; 3≤z≤5; A includes one or more of Na, K, and Mg; M includes one or more of Ni, Co, B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y includes one or more of O and F. Specifically, the positive active materials of the spinel structure include LiMn2O4, LiNi 0.5 Mn 1.5 O4、LiCr 0.3 Mn 1.7 O4、Li 1.1 Al 0.1 Mn 1.9 O4, Li2Mn2O4 and Li 1.5 One or more of Mn2O4.
[0107] The battery cell will be accompanied by the deintercalation and consumption of active ions such as Li during the charge and discharge process, and the molar content of Li in the battery cell is different when it is discharged to different states. In the list of positive electrode active materials in the embodiments of the present application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li may change after charge and discharge cycles.
[0108] In the list of positive electrode active materials in the embodiments of the present application, the molar content of oxygen O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen O to change. In reality, the molar content of oxygen O will fluctuate.
[0109] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0110] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0111] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0112] [Negative electrode]
[0113] In some embodiments, the battery cell further includes a negative electrode tab.
[0114] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0115] The negative electrode active material may be a negative electrode active material for a battery cell known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy material.
[0116] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The embodiment of the present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5wt%.
[0117] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The embodiment of the present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤5wt%.
[0118] In some embodiments, the negative electrode film layer may further include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the other additives is ≤2wt%.
[0119] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0120] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0121] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the embodiments of the present application further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector. In some other embodiments, the negative electrode plate described in the embodiments of the present application further includes a protective layer covering the surface of the negative electrode film layer.
[0122] [Electrolyte]
[0123] In some embodiments, the battery cell may further include an electrolyte.
[0124] During the charge and discharge process of the battery cell, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The embodiment of the present application has no particular limitation on the type of electrolyte, which can be selected according to actual needs.
[0125] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not specifically limited and can be selected according to actual needs.
[0126] When the battery cell of an embodiment of the present application is a lithium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0127] When the battery cell of an embodiment of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0128] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0129] In some embodiments, the electrolyte may further include additives, for example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.
[0130] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.
[0131] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0132] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0133] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0134] In some embodiments, Figure 2As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0135] The preparation method of the battery cell of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery cell is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0136] In some embodiments of the present application, the battery cells according to the present application may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module.
[0137] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0138] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0139] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0140] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0141] The battery according to the embodiment of the present application may include one battery cell or a plurality of battery cells. When the battery includes a plurality of battery cells, the battery may include a battery module or a battery pack.
[0142] Electrical devices
[0143] The fourth aspect of the embodiment of the present application provides an electric device, which includes at least one of the battery cells, battery modules or battery packs of the present application. The battery cells, battery modules or battery packs can be used as the power source of the electric device, and can also be used as the energy storage unit of the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0144] The electrical device may select a battery cell, a battery module or a battery pack according to its usage requirements.
[0145] Figure 6 Schematic diagram of an exemplary electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device 6 for high power and high energy density, a battery pack or a battery module may be used.
[0146] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0147] Example
[0148] The following embodiments describe the contents disclosed in the present application in more detail, and these embodiments are only used for illustrative explanations, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the present application disclosure. Unless otherwise stated, all parts, percentages and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0149] Preparation of Lithium Ion Batteries in Examples and Comparative Examples
[0150] 1. Preparation of positive electrode sheet
[0151] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.
[0152] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone NMP at a weight ratio of 97.5:1.4:1.1 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.
[0153] 2. Preparation of negative electrode sheet
[0154] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0155] The negative electrode active material artificial graphite, the binder styrene-butadiene rubber (SBR), the thickener sodium carboxymethyl cellulose (CMC-Na), and the conductive agent carbon black (Super P) are fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 96.2:1.8:1.2:0.8 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.
[0156] 3. Isolation film
[0157] (1) dispersing an organic compound in an NMP solvent, spraying the organic compound solution uniformly on a surface of a polyolefin PE base film (7 μm) by spraying, and then grafting an organic structure in the organic compound on the PE surface by ultraviolet light grafting to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate;
[0158] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0159] (3) Spraying a functional monomer on the modified surface (i.e., the surface having the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and after reaction, generating a functional layer on the surface of the polyolefin-based membrane, thereby obtaining an isolation membrane consisting of the functional layer and the substrate.
[0160] 4. Preparation of electrolyte
[0161] In an environment where the water content is less than 10 ppm, organic solvents ethylene carbonate EC and diethyl carbonate DMC are mixed in a volume ratio of 1:1 to obtain an electrolyte solvent, and then lithium salt and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0162] 5. Preparation of battery cells
[0163] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0164] Example 1
[0165] The lithium-ion battery is prepared by the above steps, wherein the preparation step of the isolation membrane comprises:
[0166] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0167] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0168] (3) spraying the first functional monomer m-phenylenediamine MPD (10%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0169] The n-hexane solution (5%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 20 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film composed of the functional layer and the base material.
[0170] The test showed that the grafting rate of methacrylic acid was 8.5%, and the grafting rate G = (m1-m0) / m0, where m1 is the mass of the PE film after photografting; m0 is the mass of the blank PE film (ungrafted).
[0171] Comparative Example 1
[0172] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that a polyethylene PE film (12 μm) was used as the isolation film.
[0173] Comparative Example 2
[0174] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that the steps of preparing the isolation membrane include:
[0175] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed evenly on the surface of a PE film (12 μm) by spraying, and then the methacrylic acid group was grafted by ultraviolet light grafting for 60 seconds to obtain a substrate; the photoinitiator of the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0176] (2) The substrate obtained in step (1) is treated with a 2 wt % lithium hydroxide aqueous solution, and then washed with deionized water until neutral, to obtain a lithium-based methacrylic acid group-modified polypropylene film.
[0177] Comparative Example 3
[0178] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that the steps of preparing the isolation membrane include:
[0179] Metaphenylenediamine MPD (10%) was sprayed on the surface of a polypropylene film (12 μm), and the excess aqueous monomer was removed after 30 s;
[0180] A n-hexane solution (5%) of trimesoyl chloride TMC was sprayed and reacted for 20 seconds to generate a functional layer on the surface of the polyolefin base film, thereby obtaining a separation film consisting of a functional layer and a base material.
[0181] Example 2
[0182] A lithium ion battery was prepared by a method similar to that of Example 1, except that the average pore size and thickness of the functional layer in the isolation membrane were adjusted.
[0183] Example 2-1
[0184] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the preparation method of the isolation membrane was adjusted. The preparation process of the isolation membrane was as follows:
[0185] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0186] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0187] (3) spraying the first functional monomer m-phenylenediamine MPD (9%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0188] The n-hexane solution (5%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 22 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film consisting of a functional layer and a base material.
[0189] Example 2-2
[0190] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the preparation method of the isolation membrane was adjusted. The preparation process of the isolation membrane was as follows:
[0191] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0192] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0193] (3) spraying the first functional monomer m-phenylenediamine MPD (9%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0194] The n-hexane solution (5%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 25 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film composed of the functional layer and the base material.
[0195] Example 2-3
[0196] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the preparation method of the isolation membrane was adjusted. The preparation process of the isolation membrane was as follows:
[0197] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0198] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0199] (3) spraying the first functional monomer m-phenylenediamine MPD (11%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0200] The n-hexane solution (5%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 22 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film consisting of a functional layer and a base material.
[0201] Embodiment 2-4
[0202] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the preparation method of the isolation membrane was adjusted. The preparation process of the isolation membrane was as follows:
[0203] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0204] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0205] (3) spraying the first functional monomer m-phenylenediamine MPD (12%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0206] The n-hexane solution (5%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 25 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film composed of the functional layer and the base material.
[0207] Embodiment 2-5
[0208] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the preparation method of the isolation membrane was adjusted. The preparation process of the isolation membrane was as follows:
[0209] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0210] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0211] (3) spraying the first functional monomer m-phenylenediamine MPD (13%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0212] The n-hexane solution (5%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 25 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film composed of the functional layer and the base material.
[0213] Embodiment 2-6
[0214] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the preparation method of the isolation membrane was adjusted. The preparation process of the isolation membrane was as follows:
[0215] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0216] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0217] (3) spraying the first functional monomer m-phenylenediamine MPD (13%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0218] The n-hexane solution (6%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 30 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film consisting of a functional layer and a base material.
[0219] Embodiment 2-7
[0220] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the preparation method of the isolation membrane was adjusted. The preparation process of the isolation membrane was as follows:
[0221] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0222] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0223] (3) spraying the first functional monomer m-phenylenediamine MPD (14%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0224] The n-hexane solution (6%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 38 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film consisting of a functional layer and a substrate.
[0225] Embodiment 2-8
[0226] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the preparation method of the isolation membrane was adjusted. The preparation process of the isolation membrane was as follows:
[0227] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0228] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0229] (3) spraying the first functional monomer m-phenylenediamine MPD (15%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0230] The n-hexane solution (7%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 46 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film consisting of a functional layer and a substrate.
[0231] Embodiment 2-9
[0232] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the preparation method of the isolation membrane was adjusted. The preparation process of the isolation membrane was as follows:
[0233] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was sprayed uniformly on the surface of a polyolefin PE base film (7 μm) by spraying, and then the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting, and the grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate; the photoinitiator in the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm;
[0234] (2) treating the substrate obtained in step (1) with a 2 wt % lithium hydroxide aqueous solution, and then washing with deionized water until neutral, to obtain a lithium-based organic structure-modified polyolefin-based membrane;
[0235] (3) spraying the first functional monomer m-phenylenediamine MPD (17%) on the modified surface (i.e., the surface with the organic structure) of the polyolefin-based membrane modified with the lithium-based organic structure, and removing the excess aqueous phase monomer after 30 seconds;
[0236] The n-hexane solution (8%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 55 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film consisting of a functional layer and a substrate.
[0237] Example 3-1 and Example 3-2
[0238] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the types of functional layers in the substrate in the isolation membrane were adjusted in Examples 3-1 and 3-2.
[0239] Example 4-1 to Example 4-4
[0240] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the mass percentage of the organic structure in the substrate in the isolation membrane was adjusted in Examples 4-1 to 4-4.
[0241] Example 5-1 and Example 5-2
[0242] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the types of organic structures in the substrate in the isolation membrane were adjusted in Examples 5-1 and 5-2.
[0243] Example 6
[0244] A lithium ion battery was prepared by a method similar to that of Example 1, except that the type of organic structure in the substrate of the isolation film was adjusted. (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent. The methacrylic acid solution was sprayed evenly on the surface of a polyolefin PE base film (7 μm). Then, the organic structure in the organic compound was grafted on the PE surface by ultraviolet light grafting. The grafting time was 60 s to obtain a polyolefin base film modified with an organic structure, thereby obtaining a substrate. The photoinitiator of the grafting process was benzophenone, the light source was a 500 W high-pressure mercury lamp, and the distance between the ultraviolet lamp and the surface of the PE base film was fixed at 30 cm.
[0245] (2) spraying the first functional monomer m-phenylenediamine MPD (10%) on the modified surface of the polyolefin-based film modified with the organic structure (i.e., the surface with the organic structure), and removing the excess aqueous phase monomer after 30 seconds;
[0246] The n-hexane solution (5%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 20 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film composed of the functional layer and the base material.
[0247] Example 7
[0248] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the arrangement of the organic structure in the substrate in the isolation film was adjusted (the organic structure was directly coated on the surface of the substrate).
[0249] (1) 10 g of methacrylic acid was weighed and dispersed in 200 g of NMP solvent, and the methacrylic acid solution was evenly sprayed on the surface of a PE film (7 μm) by spraying, and then dried to obtain a substrate;
[0250] (2) spraying the first functional monomer m-phenylenediamine MPD (10%) on the modified surface of the polyolefin-based film modified with the organic structure (i.e., the surface with the organic structure), and removing the excess aqueous phase monomer after 30 seconds;
[0251] The n-hexane solution (5%) of the second functional monomer trimesoyl chloride TMC was sprayed and reacted for 20 seconds to form a functional layer on the surface of the polyolefin base film, thereby obtaining an isolation film composed of the functional layer and the base material.
[0252] The relevant parameters of the embodiments and comparative examples are shown in Table 1.
[0253] Test Section
[0254] 1. Cycle performance test of lithium-ion batteries
[0255] At 25°C, the lithium-ion battery is charged to 4.25V at 2C constant current, then charged to 0.05C at 4.25V constant voltage, and then discharged to 2.8V at 1C constant current. This is a charge and discharge cycle. Taking the capacity of the first discharge as 100%, calculate the capacity retention rate of the battery after 500 cycles. The capacity retention rate of the battery after 500 cycles (%) = discharge capacity of the 500th cycle / capacity of the first discharge × 100%.
[0256] 2. K value test
[0257] The K value can be used to describe the physical quantity of the self-discharge rate of a battery cell. It can be calculated by dividing the open circuit voltage difference between two tests by the time interval △t between the two voltage tests. The formula is: K = (OCV2-OCV1) / △t. That is, K can represent the voltage drop per unit time. Generally speaking, the larger the K value, the faster the open circuit voltage drops or the larger the amplitude is, and there may be a micro-short circuit in the battery cell.
[0258] Test Results
[0259] The test results are shown in Table 1.
[0260] Table 1
[0261]
[0262]
[0263] In Table 1, the K value represents the K value obtained by testing at a time interval of 14 days.
[0264] It can be seen from Table 1 that compared with Comparative Example 1, Comparative Example 2 sets a chelating group on the substrate, and the chelating group can chelate transition metal ions, but there is a risk of desorption of transition metal ions. Comparative Example 3 sets a functional layer outside the substrate, and the functional layer can intercept transition metal ions to a certain extent, but the interception effect is relatively weak.
[0265] The functional layer of the embodiment of the present application has a positive charge, which can produce a strong electrostatic repulsion force on the transition metal ions, and the transition metal ions are more likely to be retained by the functional layer on the side of the functional layer facing the positive electrode plate; the chelating groups contained in the substrate can combine with the transition metal ions through coordination to form a chelate, and stabilize the transition metal ions in the chelate, further reducing the risk of transition metal ions migrating to the negative electrode plate, and alleviating the risk of transition metal ions precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, thereby improving the cycle performance of the battery cell.
[0266] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A separation film, comprising: A substrate, comprising a polymer film and an organic structure connected to a surface of the polymer film, wherein the organic structure comprises a chelating group; and A functional layer is disposed on at least one side of the substrate, wherein the functional layer includes positively charged groups.
2. The isolation film according to claim 1, wherein: The functional layer comprises a porous structure, and the average pore size of the porous structure is a nanometer-scale pore size; Optionally, the average pore size of the porous structure is 1.0 nm to 3.0 nm.
3. The isolation film according to claim 1 or 2, wherein: The thickness of the functional layer is 10 nm to 50 nm.
4. The separator according to any one of claims 1 to 3, wherein: The positively charged group comprises at least one of an imide group, an amide group and an imine group; Optionally, the functional layer containing the imide group comprises at least one of polyimide and polyetherimide; The functional layer containing the amide group comprises at least one of polyamide, polyetheramide, polyacrylamide, polyarylethersulfoneamide and polyarylethersulfideketoneamide; The functional layer containing the imine group includes at least one of polyethyleneimine and polymethacrylimine.
5. The separator according to any one of claims 1 to 4, wherein: The organic structure is disposed on the surface of the polymer film; or The organic structure is grafted onto the surface of the polymer film.
6. The separator according to any one of claims 1 to 5, wherein: Based on the total mass of the substrate, the mass percentage of the organic structure is 2% to 10%.
7. The separator according to any one of claims 1 to 6, wherein: The chelating group may include at least one of a carboxyl group and an imino group; Optionally, the organic structure containing the carboxyl group includes at least one of ammonium acrylate, 2-methyl-2-acrylate ammonium salt, methacrylic acid, butenoic acid, 3-methylbutenoic acid, 4-methyl-3-pentenoic acid and (E)-4-(4-methylpiperazine-1-yl)2-butenoic acid; Optionally, the organic structure containing an imino group includes at least one of iminodiacetic acid, diethyl iminodiacetate, iminotriacetic acid), 3,3'-iminodipropionic acid, disodium iminodiacetate and 3-[(aminoiminomethyl)thio]propionic acid.
8. The separator according to any one of claims 1 to 7, wherein: The weight average molecular weight of the organic structure is less than or equal to 1000Da; it can be optionally 100Da to 900Da.
9. The separator according to any one of claims 1 to 8, wherein: The thickness of the substrate is less than or equal to 16 μm, and can be 5 μm to 14 μm.
10. The separator according to any one of claims 1 to 9, wherein: The polymer membrane comprises at least one of a polyolefin and an ionomer; Optionally, the polyolefin-based polymer includes at least one of polyethylene, polypropylene and polyvinylidene fluoride; Optionally, the ionic polymer includes at least one of polyethyleneimine, polyethyleneamine, polyphosphazene and polyoxymethylene.
11. A battery comprising the separator according to any one of claims 1 to 10.
12. An electrical device comprising the battery as claimed in claim 11.
Citation Information
Patent Citations
Preparation method and application of polyolefin / nanocrystal cellulose composite diaphragm
CN105185940A
Lithium ion battery
CN107528086A
Electrochemical cells with ionic sequestration provided by porous separators
CN109804496A
Functionalized isolating membrane and lithium metal battery
CN112310559A
Composite electrolyte, protective film including composite electrolyte, protected negative electrode including the protective film, and lithium metal battery including the protected negative electrode
US20190181435A1